The Potential of Sugarcane Bagasse (Saccharum officinarum Linn.) as a Basic Ingredient for Making Cosmetics and Its Effectiveness as an Exfoliator and Skin Moisturizer - Suhesti, Iin; Sari, Yunita Dian Permata; Oktofiani, Fauziyah; Janah, Aprillia Nurul (Universitas Ahmad Dahlan, 2024)
Sugarcane bagasse (Saccharum officinarum Linn.) contains most of the phenolic compounds including gallic acid, ferulic acid, epicatechin, quercetin, and kaempferol. Various phenolic compounds contained in sugarcane bagasse, especially phenolic acids, have important bioactivity for the cosmetics industry. The aim of this research is to determine the potential of sugarcane bagasse as an active ingredient in cosmetics and its effectiveness as an exfoliator and skin moisturizer. This research method is experimental, using sugarcane bagasse samples with concentrations of 1%, 3% and 5%. The results of phytochemical screening showed that sugarcane bagasse contains phenolic compounds, flavonoids and phytosterols. Based on the research results, sugarcane bagasse exfoliating gel at concentrations of 1%, 3%, and 5% increased skin tone respectively, namely 1.00 ± 0.67; 0.40±0.49; and 0.30 ± 0.39. Sugarcane bagasse moisturizing gel at concentrations of 1%, 3%, and 5% had a percent increase in skin water content, respectively, namely 6.92 ± 11.094; 2.72±10.21; and 3.36 ± 6.49. Based on SPSS analysis, it is known that variations in the concentration of bagasse extract and the time of use have a significant effect on increasing skin tone. Meanwhile, variations in the concentration of bagasse extract did not have a significant effect on increasing skin water content. However, the time of use has a significant effect on the increase in skin water content. So, it can be concluded that sugarcane bagasse extract has the potential to be an active ingredient in making cosmetics and is effective as an exfoliator and skin moisturizer.